Pharmacokinetic Interaction Between Fingolimod and Carbamazepine in Healthy Subjects. Issue 6 (25th April 2018) - David, Olivier J.; Behrje, Rhett; Pal, Parasar; Hara, Hisanori; Lates, Christian D.; Schmouder, Robert
Abstract: This open‐label, single‐sequence study in healthy subjects investigated the effects of steady‐state carbamazepine on the pharmacokinetic (PK) profile of a single 2‐mg dose of fingolimod. In period 1, a single oral dose of fingolimod 2 mg (day 1) was followed by PK and safety assessments up to 36 days. In period 2, carbamazepine was administered in flexible, up‐titrated doses (600 mg twice daily maximum) for 49 days. Fingolimod was administered on day 35, followed by a study completion evaluation (day 71). The PK analysis included 23 of 26 of the enrolled subjects (88.5%). Coadministration of fingolimod at steady‐state carbamazepine concentrations resulted in increased fingolimod CL/F by 67% through the induction of CYP3A4, a cytochrome with negligible involvement in fingolimod clearance in an uninduced state. Fingolimod Cmax was reduced by 18% and AUCinf by 40%, as was T1/2 (106 vs 163 hours). A similar trend was observed for fingolimod‐P. Models linking fingolimod‐P blood concentrations to lymphocyte count or annual relapse rate suggest that such a decrease would have a low impact on the treatment effect. However, in the absence of efficacy data of fingolimod at doses lower than the therapeutic dose, their coadministration should be used with caution.